Types of true bugs (Insecta, Hemiptera, Heteroptera) deposited in the Museo de La Plata, Argentina - Coscarón, María Del Carmen; Basset, Carina; Lopez, Nancy (Zootaxa, 2015)
A checklist of Heteroptera type specimens deposited in the collection of División Entomología, Museo de La Plata. It harbours type material of 1153 species belonging to 37 families (Enicocephalidae, Schizopteridae, Gerridae, Veliidae, Hydrometridae, Naucoridae, Belostomatidae, Nepidae, Corixidae, Notonectidae, Pleidae, Saldidae, Cimicidae, Polyctenidae, Nabidae, Miridae, Tingidae, Vianaididae, Thaumastocoridae, Reduviidae, Aradidae, Alydidae, Coreidae, Rhopalidae, Berytidae, Blissidae, Lygaeidae, Oxycarenidae, Rhyparochromidae, Idiostolidae, Largidae, Pyrrhocoridae, Anthocoridae, Cydnidae, Pentatomidae, Scutelleridae, Thyreocoridae), represented by 207 holotypes, 26 allotypes, 578 paratypes, 1 lectotype, 1 paralectotype and 340 syntypes. For each taxon providing update information on valid names, categories of types, and locality.